(untitled) (Canadian Medical Education Journal, 2026)
Implication Statement Is your resident call schedule fairly distributed between your residents? We thought so for Family Medicine in Saskatchewan, but an analysis of two years of schedule data indicated otherwise. Over the two-year program, the average per-resident call burden ranged from 0.44 to 1.2 shifts per week. Using the ratio of total shifts to total weeks to consistently quantify resident call burden across sites, we highlight the value of longer-term metrics and demonstrate how other institutions may also develop more equitable call schedules.